Inducing salt stress tolerance in bitter gourd (Momordica chanrantia) through seed treatment with chitosan - Ali, Ahsan; Ferdosi, Fiaz Hussain; Sarwar, Mubeen; Anjum, Sumreen; Mushtaq, Zain; Liaquat, Mehwish; Abbas, Muhammad Taqqi; Anees, Moazzam; Tariq, Muhammad Rizwan; Ashraf, M. Irfan; Alasmari, Abdulrahman; Mondol, Md Sabir Ahmed; et al. (Frontiers in Plant Science, 2025)
BackgroundBitter gourd requires well-drained sandy to sandy loam soils for optimum growth, development, and germination, while its growth is retarded in extreme saline conditions. It is very sensitive to salinity stress, which imposes devastating limits on its productivity. Thus, the impact of soil salinization on the economics of bitter gourd yield deserves scientific inquiry. MethodsThe present study was designed to evaluate the various morphological attributes (mean germination time, germination index, final emergence percentage, measurements of root length, measurement of shoot length, measurement of plant dry biomass, and measurement of plant fresh biomass), physiological attributes (leaf chlorophyll content and electrolyte leakage), biochemical attributes (proline contents, antioxidant enzymes, superoxide dismutase, catalase Q9 , and peroxidase), leaf water relations (leaf osmotic potential, leaf water potential, leaf turgor potential, and leaf relative water content), and ion concentrations (Na+, K+, Ca +, and Cl-) that can be used for the evaluation of salt stress tolerance potential in bitter gourd. The research was conducted in the field area of the Faculty of Agricultural Sciences, University of the Punjab, Lahore. ResultsIn this experiment, bitter gourd seeds were sowed either without treatment or with hydropriming, 0.01%, 0.02%, 0.03%, 0.04%, and 0.05% chitosan, respectively, under 50mM soil salinity under the climatic conditions of Lahore. This research was designed to find the role of chitosan in inducing salt stress tolerance in bitter gourd plants and also find the best chitosan dose that is useful for higher salinity conditions. Different attributes of bitter gourd were recorded. Results revealed that chitosan application at 0.04% is best for enhancing the salt stress tolerance potential of bitter gourd. Different morphological attributes, physiological attributes, water relation attributes, and biochemical parameters were also recorded. It was observed that pre-sowing treatments with an optimized dose of 0.04% chitosan exhibited significant effects on all the bitter gourd plants and improved the germination rate by improving the salt stress tolerance potential of plants under high salinity. ConclusionIt can be concluded from the present research that the optimized dose of 0.04% chitosan has also proved effective in the enzymatic activity of bitter gourd by enhancing the salt stress potential under increasing salt stress.